Turkey's First Female Diplomat: Adile Ayda (Universal International Scientific Journal, 2026)
The early years of the Turkish Republic witnessed many changes in political life. During this process, Turkish diplomacy also opened its doors to women. Adile Ayda became Turkey's first female diplomat when she was appointed as a career officer at the Ministry of Foreign Affairs in 1932. However, Adile Ayda's diplomatic career was turbulent. In her own words, she withdrew from the world of diplomacy for a while "due to some obstacles she faced because of being a woman," and after a while she returned to the diplomatic profession.
Keywords: Adile Ayda, Turkish Diplomacy, Ministry of Foreign Affairs, Women Diplomats.